Pengaruh Latihan Running With The ball terhadap Peningkatan Keterampilan Dribbling Pemain Sepak Bola Usia 13-15 Tahun di Sekolah Sepak Bola (SSB) SINGOJOYO Kabupaten Malang - Moch. Maulidan; Supriyadi Supriyadi; Ardhiyanti Puspita Ratna (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
It can be seen that this study has one goal, namely to determine the effeck of running with the ball exercise on improving the dribbling skill of SBB Singojoyo football players, Malang Regency. This study used a sample off all 13-15 years old SSB Singojoyo soccer athletes in Malang, totaling 20 people using a sampling technique. In this study, the experimental method was applied, with the One-Group Pretest-Postest experimental design. The instrument used is the Test Course of the Sport Dribbling test which is used during the pretest dan posttest. The results of this study used the normality test and paired sample t test, which showed that there was a significant effect on improving dribbling skills by giving running with the ball exercises. This can be seen by looking at the results of data analysis on the calculation of the t test which shows that t count is greater than t table (4,162>2,093) with a significance test (∝) = 0.05 and a total sample (N = 20), the hypothesis is accepted and has an effect. Based on the results of the study it can be concluded that running with the ball exercise has a significant influence of tge dribbling skills of SSB Singojoyo Malang Regency aged 13-15 years.